Benefits of Implementing Mobile Phone-Based Self-Management Interventions in Coronary Heart Disease Patients on Medication Adherence and Reducing Blood Pressure - Risa Oktavina; Wati Jumaiyah; Dhea Natashia; Yani Sofiani; Sumedi Sumedi (GLOBAL HEALTH SCIENCE GROUP, 2024)
Coronary Heart Disease (CHD) is a non-communicable disease that is a public health problem and the number is increasing both in the world and in Indonesia. So good self-management skills are needed in effort to improve the patient's ability to manage CHD risk factors, compliance with taking medication and achieving reduced blood pressure. The development of technology makes the use of mobile phones a necessity. Therefore, mobile phone-based self-management interventions are expected to be effective in improving patients' ability to self-manage to achieve medication compliance and reduce blood pressure. Increased compliance with taking medication and a decrease in blood pressure. The design used is a case study with an innovative design in the form of applying research results regarding mobile phone-based self-management interventions for coronary heart disease patients. The self-management intervention took the form of personal education using e-booklets and short WhatsApp text messages for 8 weeks. And the standard questionnaire consists of MMAS8 and SCC HDI. It is known that there is a decrease in systolic blood pressure (SBP) and diastolic blood pressure (DBP), as well as a decrease in total cholesterol levels. Apart from that, there was an increase in patient medication adherence scores and an increase in the self-management ability of CHD patients. There was a significant effect of mobile phone-based self-management intervention on medication adherence, SBP and DBP values, total cholesterol, and self-management abilities.